2021
DOI: 10.21203/rs.3.rs-426688/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impact-crater ejecta on Bennu indicate a surface with very low strength

Abstract: A planetary surface’s resistance to change is generally described as its “strength” (units of stress). The surface strength of small, rubble-pile asteroids, which consist of fragments of larger bodies that were collisionally disrupted, is poorly constrained due to their wide departure from terrestrial analogs. Here, we report the observation of an ejecta deposit surrounding an impact crater that limits the maximum surface strength of the near-Earth rubble-pile asteroid (101955) Bennu. The presence of this depo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…According to the FS analysis, the regions of current failure are primarily above 30° of latitude in both the northern and southern hemispheres. These areas are where evidence for surface flows (Barnouin et al, 2019;Jawin et al, 2020;Perry et al, 2022;Walsh et al, 2019) and the terraces described here are observed.…”
Section: Slope Stability Analysismentioning
confidence: 62%
See 1 more Smart Citation
“…According to the FS analysis, the regions of current failure are primarily above 30° of latitude in both the northern and southern hemispheres. These areas are where evidence for surface flows (Barnouin et al, 2019;Jawin et al, 2020;Perry et al, 2022;Walsh et al, 2019) and the terraces described here are observed.…”
Section: Slope Stability Analysismentioning
confidence: 62%
“…As a endmember case (Figure 8), we use c = 1 Pa with the plausible ϕ = 40° and T = 3 m. This thickness is derived from the depths of mounds at the centers of three craters on Bennu (R. T. Daly et al., 2020), which offer one direct measure of the approximate depth of the unconsolidated surface layer (Quaide & Oberbeck, 1968). But geomorphic assessments of mass movement (Jawin et al., 2020; Perry et al., 2022) elsewhere on Bennu indicate that surface debris with thicknesses of up to 10 m are readily mobilized. We therefore consider lower values of c ≥ 0.1 for a broader range of plausible surface debris thicknesses (Figure 9), with ϕ = 34° and 40°.…”
Section: Slope Stability Analysismentioning
confidence: 99%